2018
DOI: 10.1002/net.21834
|View full text |Cite
|
Sign up to set email alerts
|

Detecting critical node structures on graphs: A mathematical programming approach

Abstract: We consider the problem of detecting a collection of critical node structures of a graph whose deletion results in the maximum deterioration of the graph's connectivity. The proposed approach is aimed to generalize other existing models whose scope is restricted to removing individual and unrelated nodes. We consider two common metrics to quantify the connectivity of the residual graph: the total number of connected node pairs and the size of the largest connected component. We first discuss the computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 79 publications
(138 reference statements)
1
11
0
Order By: Relevance
“…Most of the participants confirmed that the nodes with extremely high degrees had a strong visual saliency, which was in line with the previous research that stated that visually salient high degree nodes should not be lower than the global top 10% [57]. In general, high degree nodes have two subtypes [71], namely, pivot and star. A pivot is a high degree node whose neighbors have at least one interconnection.…”
Section: Results Analysissupporting
confidence: 88%
“…Most of the participants confirmed that the nodes with extremely high degrees had a strong visual saliency, which was in line with the previous research that stated that visually salient high degree nodes should not be lower than the global top 10% [57]. In general, high degree nodes have two subtypes [71], namely, pivot and star. A pivot is a high degree node whose neighbors have at least one interconnection.…”
Section: Results Analysissupporting
confidence: 88%
“…The focus is to identify the most critical nodes/arcs susceptible of making the maximum disturbance on the network performance once disabled. In this context, Walteros et al [18] discuss a framework to detect the set of critical nodes that maximize the possibility of disconnecting the network. Karakose and McGarvey [19] propose a path-based formulation and multi-commodity flow-based formulations to identify the optimal k-nodes to be attacked on a directed flow network so that to maximize the network disruption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In practice, this corresponds to a situation where, most of the time, only same‐group vertices communicate to each other and most of the information that a vertex can receive comes from inside the same group to which it belongs. These groups may correspond to large cliques or quasi‐cliques (Abello et al., 1999; Pinto et al., 2018; Ribeiro and Riveaux, 2018; Vogiatzis and Walteros, 2018; Walteros et al., 2019). In such graphs, there may be an important number of vertices that are loosely connected to other groups, that is, there may be only intragroup edges adjacent to these vertices.…”
Section: Motivationmentioning
confidence: 99%